Skull base “intrinsic” bony mass lesions: conventional, diffusion and perfusion imaging with a proposed imaging approach - Lamya Eissa; Rim Aly Bastawi (The Egyptian Journal of Radiology and Nuclear Medicine, 2024)
Abstract Background and purpose Imaging with conventional MRI plays a pivotal role in characterization of skull base bone-intrinsic lesions, yet some lesions are very challenging. The purpose of this study is to evaluate the role of diffusion and perfusion by T2* dynamic susceptibility contrast (DSC) in characterization of such lesions. Results Lesions showed mostly correlated with approach: Chordomas had low perfusion and intermediate to high perfusion, while chondrosarcoma had ADC value > 1.6 × 10–3/cm2 and more perfused. Metastases had variable ADC values usually intermediate with high perfusion. Plasmacytomas had similar features yet with characteristic conventional morphology and single number. Lymphoma (primary bony) had high perfusion and lowest diffusion ADC (= 04–0.7 × 10–3/cm2). Giant cell tumors and hemangiopericytomas had lowest perfusion. Conclusion The proposed imaging approach showed very good results and high accuracy in differentiation of skull base bony lesions.